Exhibition Ethics - An Overview of Major Issues. Issue 1 (8th May 2014) - Gazi, Andromache
Museum ethics are about value judgements. In making such judgements museum personnel is constantly valuing one option over another. This holds true for every aspect of museum work; from collecting policies and conservation to store priorities and exhibition. In recent decades there has been a growing concern in addressing ethical issues in museums as museum workers have developed cultural sensitivity and social responsiveness to a degree unseen before. Most codes of ethics urge museums to give appropriate consideration to represented groups or beliefs. In light of this, it has been recognised that exhibition of sensitive material, for example, must be done with great tact and respect for the feelings of religious, ethnic or other groups represented. Another issue concerns the display of unprovenanced material and repatriation. Yet, these are not the only ethical issues which exhibition developers are faced with. As museum workers we should constantly be reminded that exhibitions are active agents in the construction of knowledge. This paper discusses the hidden assumptions on which museum presentation and interpretation are often based. Decisions about what to include and what to exclude, what is valued and what is not, the means of presentation, language, and so on, all lead to presentational styles which may shape the public's perception in unintended ways.